Assessment of the Health Workers Knowledge About Nutrition in an University Hospital - Mehmet Turan İnal; Dilek Memiş; Murat Kargı; Necdet Süt (Galenos Yayinevi, 2010)
Objective: Clinicians must know the definitions of malnutrition for diagnose and early treatment. This study assessed the knowledge of anesthesia residents, surgery residents and intensive care nurses about nutrition that are usually studied on the patients with malnutrition. Materials and Methods: We applied a inquiry to 80 residents and nurses working in an university hospital. The inquiry was consist of 20 questions about nutritional aspects, oral/enteral nutrition and parenteral nutrition. The one-way ANOVA, Kruskal-Wallis and chi-squre tests were used to compare variables between groups. Results: Anaesthesists group scored significantly than other groups in questions about nutritional aspects. Statistically difference was detected between anaesthesists group and intensive care nurses group (p<0.05). Surgery residents group scored more than other groups in oral/enteral nutrition questions, and statistically difference was detected between surgery residents group and surgery intensive care nurses group (p<0.05). Anaesthesists group scored significantly than other groups in questions about parenteral nutrition. Statistically difference was detected between anaesthesists group and intensive care nurses group (p<0.05). Conclusion: Knowledge about nutrition among residents and nurses was poor. Clear diagnosis and definition of nutrition and malnutrition must be defined clearly by all disciplines during training of the residents and intensive care nurses. (Journal of the Turkish Society of Intensive Care 2010; 8: 66-72)